Comparative effect of allopurinol and febuxostat on long-term renal outcomes in patients with hyperuricemia and chronic kidney disease: a systematic review - Hu, Anna M.; Brown, Jamie N. (Clinical rheumatology, 2020)
Patients with chronic kidney disease (CKD) are more likely to develop hyperuricemia and gout. Allopurinol and febuxostat are the most commonly used urate-lowering therapies with established safety and efficacy in CKD patients. The objective of the systematic review is to assess the long-term renal outcomes of allopurinol compared with febuxostat in patients with hyperuricemia and CKD or kidney transplantation. PubMed MEDLINE, Embase, Web of Science, Scopus, and Cochrane CENTRAL databases were searched from inception to December 2019 using the key terms “allopurinol,” “febuxostat,” “xanthine oxidase inhibitors,” “gout suppressants,” “hyperuricemia,” “gout,” “chronic renal insufficiency,” and “kidney transplantation.” Studies with follow-up duration ≥ 12 months were included. Risk of bias was assessed using the Cochrane Risk Of Bias In Non-randomized Studies-of Interventions (ROBINS-I) tool. Three retrospective observational studies with follow-up duration ranging from 1 to 5 years were reviewed. Febuxostat patients had a significantly higher estimated glomerular filtration rate, reduced risk for renal disease progression, and reduced serum uric acid levels compared with allopurinol patients. All studies had a serious risk of bias. Febuxostat may be more renoprotective than allopurinol in patients with both hyperuricemia and CKD based on evidence from small long-term retrospective studies with serious risk of bias. More methodologically rigorous studies are needed to determine the clinical applicability of these results.